Student Learning Strategies in Second Language Acquisition of English: Empirical Study of Private University Student in Pandeglang District - Riandi, Riandi; Nupus, Hayati (Universitas Mathla'ul Anwar Banten, 2021)
The importance of learning English as a foreign language or second language in the university environment, as it is known that English is a widely spoken language all over the world, however, inefficient learning of English is a tremendous problem for many English departments in the English language. Apart from the linguistic environment, the lack of an effective strategy guide is also one of the main factors causing this problem. To find out whether the use of language learning strategies helps the speaking ability of students in English departments or not, in this study, fifteen students in English departments were surveyed with a questionnaire about learning English and using their strategies. It was found that most students in this private university used metacognitive learning strategies with an index of 3.80, and compensation and affective strategies were used the least with an index of 2.67 while cognitive strategies were used almost frequently but sometimes memory and social strategies were used by students a private university student in English departments in this Pandeglang district. In other words, the use of learning strategies helps students' English skills there. Therefore, to improve students' English, this paper proposes that lecturers systematically guide students in learning strategies.